2021
DOI: 10.1063/5.0048809
|View full text |Cite|
|
Sign up to set email alerts
|

Phase stability of colloidal mixtures of spheres and rods

Abstract: We determined the phase boundaries of aqueous mixtures containing colloidal rod-like fd-viruses and polystyrene spheres using diffusing-wave spectroscopy and compared the results with free volume theory predictions. Excluded volume interactions in mixtures of colloidal rods and spheres lead to mediated depletion interactions. The strength and range of this attractive interaction depend on the concentrations of the particles, the length L and diameter D of the rods and the radius R of the spheres. At strong eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 73 publications
(104 reference statements)
0
15
0
Order By: Relevance
“…Here, we outline the FVT employed in this paper, which is based on previous work on binary HS mixtures 15 but extended to take the anisotropic shape of rod-like depletants into account. 27 In FVT the two compartments used are in osmotic equilibrium and the thermodynamic properties of the system can be described by the semi-grand potential Ω . The experimental system of interest here is the mixture of hard spheres (s) and hard rod-like depletants (r).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we outline the FVT employed in this paper, which is based on previous work on binary HS mixtures 15 but extended to take the anisotropic shape of rod-like depletants into account. 27 In FVT the two compartments used are in osmotic equilibrium and the thermodynamic properties of the system can be described by the semi-grand potential Ω . The experimental system of interest here is the mixture of hard spheres (s) and hard rod-like depletants (r).…”
Section: Methodsmentioning
confidence: 99%
“…Comparison with the FVT by Vliegenthart and Lekkerkerker 17 showed that FVT predicts phase transitions at too low colloidal rod concentrations. 27 More recently, it was shown that experimentally observed phase boundaries in mixtures of fd-virus and polystyrene spheres can be described more accurately by FVT with excluded volume interactions already included at the level of the reservoir. 27 This novel FVT method is a relatively simple and quick method to predict the phase boundaries of colloidal mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Slender rods are far more effective depletant than the commonly used polymers, as also the orientational entropy is strongly reduced when rods are confined between two cells [37][38][39]. As such the rod-like virus is a pure depletant that induces long-ranged attraction at very low volume fractions, inducing a depletion force that can be tuned by varying the concentration of these rods [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%